1990
DOI: 10.1139/v90-185
|View full text |Cite
|
Sign up to set email alerts
|

Application of FT-Raman spectroscopy to the study of selected organometallic complexes and proteins

Abstract: The study of colored organometallic complexes by dispersive Raman spectroscopy has been limited due to fluorescence or photodecomposition caused by the visible laser used as the excitation source. As a solution to this problem, IT-Raman spectroscopy with a near-infrared laser source has been useful in lowering fluorescence or photolysis in these samples. To investigate the utility of this technique, we have obtained and assigned the FT-Raman spectra of a series of arene chromium tricarbonyl complexes and of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…12, JUNE determine unsaturation in natural oils and fats (280), to study photobiological systems (281) and photoactive proteins (282) and its general application to biological materials has been discussed (283). Other applications have related to the study of selected proteins (284), human lenses (285), the analysis of pharamceuticals and biomaterials (286) and studies of human arteries (287). Other instrumental and technique developments relating to biological studies that have been reported are an automated spectrometer for the precise recording of polarized Raman spectra of biopolymers and their components (288), a commercial anesthetic-respiratory gas monitor (289), and the use of confocal Raman spectroscopy to study single living cells and chromosomes ( 290).…”
Section: Biological Systemsmentioning
confidence: 99%
“…12, JUNE determine unsaturation in natural oils and fats (280), to study photobiological systems (281) and photoactive proteins (282) and its general application to biological materials has been discussed (283). Other applications have related to the study of selected proteins (284), human lenses (285), the analysis of pharamceuticals and biomaterials (286) and studies of human arteries (287). Other instrumental and technique developments relating to biological studies that have been reported are an automated spectrometer for the precise recording of polarized Raman spectra of biopolymers and their components (288), a commercial anesthetic-respiratory gas monitor (289), and the use of confocal Raman spectroscopy to study single living cells and chromosomes ( 290).…”
Section: Biological Systemsmentioning
confidence: 99%